1988
DOI: 10.1080/03015521.1988.10425610
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of potassium losses from a grazed dairy farm in Taranaki

Abstract: The potassium (K) lost through animal products (milk, calf and culled stock) and transfer of excretal K to the dairy shed and raceways, was estimated at 1.6 kg/stock unit (SU) for a dairy farmlet of small herd size, assuming the cows spend 5070 of the year off the paddock. This loss increased to 2.5 kg K/SU if the cows spend 10070 of the year off the paddock as is likely on a dairy farm with a larger number of cows. These values are lower than the 4 kg K/SU currently used by the Ministry of Agriculture and Fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Despite this lack of K retention, K losses through leaching (8-24 kg K ha-1 yr-1 ) were not high enough to account for the difference. Animal losses from milk and excreta deposited off the paddocks, averaged over all farmlets, were estimated to be 42 kg K ha-1 yr-1 (Williams & Roberts 1988). No fertiliser K was applied after April 2001 so there was a net deficit of 50-66 kg K ha-1 yr -1 , but this would not have been expected to reduce soil K levels on K2 and K3 to that extent.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this lack of K retention, K losses through leaching (8-24 kg K ha-1 yr-1 ) were not high enough to account for the difference. Animal losses from milk and excreta deposited off the paddocks, averaged over all farmlets, were estimated to be 42 kg K ha-1 yr-1 (Williams & Roberts 1988). No fertiliser K was applied after April 2001 so there was a net deficit of 50-66 kg K ha-1 yr -1 , but this would not have been expected to reduce soil K levels on K2 and K3 to that extent.…”
Section: Discussionmentioning
confidence: 99%
“…High Kc soils are considered to supply sufficient K for pasture, unless used excessively for hay or silage (Cornforth & Sinclair 1984 Williams (1988) studied the accuracy of prediction of the K losses in depth and tested the prediction under different situations. It was concluded that the CFAS model tends to underestimate the K losses from grazed dairy pasture via leaching by not allowing for the loss that occurs during preferential flow of urine deep into the soil profile (Williams et al 1990) and overestimates the loss of K through transfer to unproductive areas (Williams & Roberts 1988;Williams et al 1990). An improved method of estimating the losses was presented by Williams (1988) and Williams et al (1990).…”
Section: Cfas Model For Computing K Fertiliser Recommendationsmentioning
confidence: 99%
“…This test extracts solution K and c. 70% of exchangeable K. For a soil with a bulk density of 0.8 Mg/m 3 one Quick Test unit is equivalent to 0.07 me Kll00 g. Over the 8-year period of this study, there was no indication that the Quick Test extractable K content of the soil was declining (Williams & Roberts 1988) even though the total accumulated loss could have resulted in a New Zealand Journal of AgriculturalResearch, 1990, Vol. 33 drop of 10 Quick Test units (from 12 to 2) in the 0-7.5 cm samplingdepth (assumingthatpastureplants remove K equally from the 0-15 em depth of soil).…”
Section: Validation Of Modelmentioning
confidence: 79%
“…The main reason for this lack of appraisal has been the scarcity of suitabledatafrom whichto measureor estimatethe losses for a given system. Thereis, however, some evidence which suggests that the model overestimates some of the lossesof K whichoccur from grazed dairy pasture (Williams & Roberts 1988). Betterquantification of the lossesof K from dairy pastures is necessary to improve predictions of K fertiliser requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation